2020
DOI: 10.3389/fpubh.2020.559312
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in COVID-19: Addressing the Role of Social Determinants of Health in Immune System Dysfunction to Turn the Tide

Abstract: It is evident that health disparities exist during the COVID-19 pandemic, a pandemic caused by the novel coronavirus SARS-CoV-2. Underlying reasons for COVID-19 health disparities are multi-factorial. However, social determinants, including those regarding socioeconomic status, social inequalities, health behaviors, and stress, may have implications on these disparities. Exposure to one or more of these social determinants is associated with heightened inflammatory responses, particularly increases in the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 124 publications
0
24
1
1
Order By: Relevance
“…These factors disproportionately affect minorities [11] , placing them at high risk of Covid-19 infection and mortality [ 4 , 7 ]. Clinically it has been postulated that the stress levels due to low socioeconomic status, social inequalities, and unhealthy behaviors increase cytokine interleukin-6 (IL-6) and immune system dysfunction, which trigger Covid-19 complications [12] .…”
Section: Introductionmentioning
confidence: 99%
“…These factors disproportionately affect minorities [11] , placing them at high risk of Covid-19 infection and mortality [ 4 , 7 ]. Clinically it has been postulated that the stress levels due to low socioeconomic status, social inequalities, and unhealthy behaviors increase cytokine interleukin-6 (IL-6) and immune system dysfunction, which trigger Covid-19 complications [12] .…”
Section: Introductionmentioning
confidence: 99%
“…32 Access to an adequate diet is influenced by multiple parameters such as socioeconomic status or neighbourhood environment. 33 …”
Section: Discussionmentioning
confidence: 99%
“…32 Access to an adequate diet is influenced by multiple parameters such as socioeconomic status or neighbourhood environment. 33 During the first wave of the COVID-19 epidemic in Spain, social services were also overwhelmed and many local associations had to help to meet essential and home care needs to ensure a minimum level of welfare for large sections of the population. 34 The COVID-19 pandemic has highlighted the need to reinforce local administrations and to continue providing social services and programmes for engaging and supporting patients, especially the most vulnerable such as older adults, during this difficult time of physical distancing and stay-at-home orders.…”
Section: Open Accessmentioning
confidence: 99%
“…Seligman et al also found high incidence of deaths among individuals of non-white ethnicity, less than high school level of education, and veterans. Baumer et al (2020) add poor living conditions and neighborhood deprivation because they inflict psychosocial stress of individuals and cause immune system disfunction.…”
Section: Literature Reviewmentioning
confidence: 99%